Cytosolic Phospholipase A(2)-α: A Potential Therapeutic Target for Prostate Cancer - Patel, Manish I. (2008)
PURPOSE: Cytosolic Phospholipase A2-α (cPLA2-α) provides intracellular arachidonic acid to supply both cyclooxygenase and lipoxygenase pathways. We aim to determine the expression and activation of cPLA2-α in prostate cancer (PC) cell line and tissue and the effect of targeting cPLA2-α in-vitro and in-vivo. EXPERIMENTAL DESIGN: The expression of cPLA2-α was determined in PC cells by RT-PCR, Western blot and immunocytochemistry. Growth inhibition, apoptosis and cPLA2-α activity were determined after inhibition with cPLA2-α siRNA or inhibitor (Wyeth-1). cPLA2-α inhibitor or vehicle was also administered to PC xenograft mouse models. Finally the expression of phospho-cPLA2-α was determined by immunohistochemistry in human normal, androgen sensitive and insensitive PC specimens. RESULTS: cPLA2-α is present in all PC cells lines, but increased in androgen insensitive cells. Inhibition with siRNA or Wyeth-1 results in significant reductions in PC cell numbers, as a result of reduced proliferation as well as increased apoptosis and this was also associated with a reduction in cPLA2-α activity. Expression of cyclin D1 and phosphorylation of Akt were also observed to decrease. Wyeth-1 inhibited PC3 xenograft growth by approximately 33% and again, also reduced cyclin D1. Immunohistochemistry of human prostate tissue revealed that phospho-cPLA2-α is increased when hormone refractory is reached. CONCLUSIONS: cPLA2-α expression and activation is increased in the androgen insensitive cancer cell line and tissue. Inhibition of cPLA2-α results in cells and xenograft tumor growth inhibition and serves as a potentially effective therapy for hormone refractory PC.